SYMBOLISM IN THE DANCE OF KARONESE TRADITIONAL WEDDING CEREMONY - Halifah Nurhaliza Sembiring; Windy Sitorus; Hiace Vega Fernando Siahaan (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2021)
The goal of this study is to analyze the meaning of symbol from dance movements used in Karonese traditional wedding ceremony. The object of the research is the dance movements of the the bride and groom in Karonese traditional wedding ceremony.The analysis shows that the structure of the landek kerja perjabuun consists of endek (knee ups and downs movement), pengodak/odak (bodymovements) and ole or jole jemolah jemole ( hands and fingers movement). The functions of landek in the kerja perjabuun are to ratifycation social institutions, to implement norms in society, to mark the implementation of the marriage ceremony, to signify social status, to show traditional communication, and cultural continuity. The meaning of landek in kerja perjabuun is as symbolic blessing (blessing prayer) to the bride, as a connector to family relationship, respect for the presence of a person in kindship group, learning of Karo traditional norms, prestige for Karo people, an expression of excitement for the family releasing daughter who will go to other families (farewell) and show the tribal existence.